Bygones - Sawyer, Kim Vogel (Uhrichsville, OH : Barbour Publishing, 2007)
Widow Marie Koeppler and her grown daughter Beth reluctantly return to the Mennonite community Marie abandoned twenty-three years ago. Soon after their arrival in Sommerfeld, a series of mysterious thefts raises the community's suspicions against the "outsiders." Can Marie prove their innocence, or will she be forced to flee once more? Henry Braun thought he'd gotten his love for Marie out of his system, but soon begins to wonder if she's stolen more than his heart. When it's all said and done, can Henry and Marie let bygones be bygones, or has their love been doomed from the start?
Keywords: Mennonites -- Fiction; Widows -- Fiction; Christian fiction